CRUISE TOURISM : PERSAINGAN IMAGE, VALUES DAN BRANDING DESTINASI WISATA - I Nyoman Sudiarta (Jurnal Ilmiah Hospitality Management, 2011)
Cruise tourism is a part of tourism industry, which kown as floating hotel or floating resort (Dowling (2006). It’s be  a new industry in  the world, that  evidenytly the  growth of cruises principal. Such as Holland American Line, Costa Cruise dan Carnival P&O Cruises, Silversea, Tui cruises, Star cruises. This opportunities supported The Growth of people travel used of cruise line average 4,5 % annual. Hence It’s will bring  a tight competition especially in pricing play  (Papatheodorou,2006). Bali as internation destination, owning opportunity as cruise tourist destination, with various weakness require or conducted research  and  correction of  infrastructure and superstructure and also human resource that have  ability in  cruise tourism. Rivalry in the future between image and creating of value to the customer.